2019
DOI: 10.3390/nu11112575
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Ingestion Improves 5 km Cycling Performance in Men and Women by a Similar Magnitude

Abstract: Caffeine is a well-established ergogenic aid, although research to date has predominantly focused on anhydrous caffeine, and in men. The primary aim of the present study was to investigate the effect of coffee ingestion on 5 km cycling time trial performance, and to establish whether sex differences exist. A total of 38 participants (19 men and 19 women) completed a 5 km time trial following the ingestion of 0.09 g·kg-1 coffee providing 3 mg·kg-1 of caffeine (COF), a placebo (PLA), in 300 mL of water, or contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…Ingesting coffee reduced 5-km cycling time-trial completion time by 1.7 ± 2.6% (8 ± 12 s), with low users improving by 1.7 ± 2.8% (9 ± 14 s) and high users by 1.8 ± 2.0% (8 ± 10 s). These findings support Clarke et al (2019), who observed that coffee providing 3 mg/kg of caffeine improved 5-km cycling timetrial performance by 1.9% (men: 2.1% and women: 1.8%) compared with a PLA and Clarke et al (2018) where the ingestion of caffeinated coffee providing 3 mg/kg of caffeine improved 1-mile race time by 1.9% compared with a PLA. In addition, Wiles et al (1992) reported that the ingestion of 3 g of caffeinated coffee, containing approximately 150-200 mg of caffeine, improved 1500-m treadmill running performance by 4.2 s (1.4%) when compared with decaffeinated coffee.…”
Section: Discussionsupporting
confidence: 85%
“…Ingesting coffee reduced 5-km cycling time-trial completion time by 1.7 ± 2.6% (8 ± 12 s), with low users improving by 1.7 ± 2.8% (9 ± 14 s) and high users by 1.8 ± 2.0% (8 ± 10 s). These findings support Clarke et al (2019), who observed that coffee providing 3 mg/kg of caffeine improved 5-km cycling timetrial performance by 1.9% (men: 2.1% and women: 1.8%) compared with a PLA and Clarke et al (2018) where the ingestion of caffeinated coffee providing 3 mg/kg of caffeine improved 1-mile race time by 1.9% compared with a PLA. In addition, Wiles et al (1992) reported that the ingestion of 3 g of caffeinated coffee, containing approximately 150-200 mg of caffeine, improved 1500-m treadmill running performance by 4.2 s (1.4%) when compared with decaffeinated coffee.…”
Section: Discussionsupporting
confidence: 85%
“…This can partially explain the equivocal nature of previous findings on the ergogenic effects of CAF and can also explain increased TUT in the group of females compared to the decrease of TUT observed for men. Yet, this explanation remains speculative until further investigation confirms an greater effect of CAF in women vs. men in local strength-endurance tests because current evidence shows similar ergogenic benefits in cycling endurance activities [ 29 , 30 ], and a tendency for a lower effect of CAF on strength-endurance performance in female subjects [ 32 ]. However, for assessing local strength-endurance and to test the effectiveness of dietary supplements during resistance exercise, the use of crossover designs and the evaluation of not only the number of REP, but also TUT may be recommended [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some of the caffeine-induced stimulant effects are of smaller magnitude in women than in men [ 28 ]. Furthermore, two recent investigations have found that the ergogenic effect of CAF may be of similar magnitude in men and women, although these investigations were carried out under aerobic conditions lasting from approximately 6 to 60 min [ 29 , 30 ]. Hence, to date, it is unknown if the ergogenic effects of CAF related to resistance exercise performance observed in male subjects [ 1 , 2 , 5 , 31 ] apply to female athletes.…”
Section: Introductionmentioning
confidence: 99%
“…In this sample, sixteen players were men and fifteen were women. The data on the men and women were merged as the ergogenic response to caffeine is similar in both sexes [41,42]. Ten women participants were tested during the follicular phase of their menstrual cycle and five were tested during the luteal phase according to a mobile application (Mycalendar ® , Period-tracker, USA).…”
Section: Participantsmentioning
confidence: 99%